Evaluation of Caspase‐3 Activity During Apoptosis with Fluorescence Lifetime‐Based Cytometry Measurements and Phasor Analyses. Issue 12 (25th August 2020) - Nichani, Kapil; Li, Jianzhi; Suzuki, Miho; Houston, Jessica P.
Abstract: Caspase‐3 is a well‐described protease with many roles that impact the fate of a cell. During apoptosis, caspase‐3 acts as an executioner caspase with important proteolytic functions that lead to the final stages of programmed cell death. Owing to this key role, caspase‐3 is exploited intracellularly as a target of control of apoptosis for therapeutic outcomes. Yet the activation of caspase‐3 during apoptosis is challenged by other roles and functions (e.g., paracrine signaling). This brief report presents a way to track caspase‐3 levels using a flow cytometer that measures excited state fluorescence lifetimes and a signal processing approach that leads to a graphical phasor‐based interpretation. An established Förster resonance energy transfer (FRET) bioprobe was used for this test; the connected donor and acceptor fluorophore is cleavable by caspase‐3 during apoptosis induction. With the cell‐by‐cell decay kinetic data and phasor analyses we generate a caspase activation trajectory, which is used to interpret activation throughout apoptosis. When lifetime‐based cytometry is combined with a FRET bioprobe and phasor analyses, enzyme activation can be simplified and quantified with phase and modulation data. We envision extrapolating this approach to high content screening, and reinforce the power of phasor approaches with cytometric data. Analyses such as these can be used to cluster cells by their phase and modulation "lifetime fingerprint" when the intracellular fluorescent probe is utilized as a sensor of enzyme activity. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals LLC on behalf of International Society for Advancement of Cytometry.